Measuring Corporate Culture Internalization at Consumer Division of PT. Telekomunikasi Indonesia - Suryawan, Dedy; Welly, John (The Indonesian Journal of Business Administration, 2016)
Abstract - PT. Telekomunikasi Indonesia as one of the big companies and had a role in providing the telecommunication service in Indonesia realized the important role of the company culture. Telkom also since 2009 to build a corporate culture to support changes in the corporate culture. In 2013 company built a culture called The Telkom Way (TTW). PT. Telkom was doing internalization phase in 2015 for company cultural transformation. The internalization phase is where The Telkom Way are implemented thorough the company in daily operational activities. PT. Telkom after the internalization phase need to measure the result with appropriate tool to make sure the condition of implementation The Telkom Way in the organization. Cultural Transformation at PT. Telkom is in order for the company to stay competitive and to be company with high-performance culture. Hence Degree of Value Integration (DVI) and DICE Framework was used to measure and understand the current position of internalization phase. This research establish the result that most of Telkom values have achieved â€œEmbeddedâ€ by the employees in Consumer Division at PT. Telkom Indonesia. This good result is supported by the DICE Score that the change management in PT. Telkom is in the â€œWin Zoneâ€. Win Zone means that the project is statistically possibly to succeed. Although the values have a good result, still it must be maintained by the company.Â Keywords: Corporate Culture, Organization Culture Measurement, Degree of Value Integration, DICE Framework.